1999
DOI: 10.1152/ajplung.1999.277.1.l13
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus-mediated changes in airway smooth muscle responsiveness: induced autocrine role of interleukin-1β

Abstract: An important interplay exists between specific viral respiratory pathogens, most commonly rhinovirus (RV), and altered airway responsiveness in the development and exacerbations of asthma. Given that RV infection reportedly induces the release of various cytokines in different cell types and that the reported effects of RV on airway smooth muscle (ASM) responsiveness are highly comparable to those obtained in ASM exposed to the proinflammatory cytokine interleukin (IL)-1β, this study examined whether RV (serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 33 publications
4
40
0
Order By: Relevance
“…First, the flu virus infection may directly induce AHR by increasing airway smooth muscle contraction through the production of IL-1␤. Rhinovirus-induced IL-1␤-dependent increase in airway smooth-muscle contraction has been shown to occur in vitro (44), and it has been shown that flu virus infection leads to the production of IL-1␤ in the lung (45). A second possibility is that the flu virus infection induced the production of IL-13 in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…First, the flu virus infection may directly induce AHR by increasing airway smooth muscle contraction through the production of IL-1␤. Rhinovirus-induced IL-1␤-dependent increase in airway smooth-muscle contraction has been shown to occur in vitro (44), and it has been shown that flu virus infection leads to the production of IL-1␤ in the lung (45). A second possibility is that the flu virus infection induced the production of IL-13 in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…One potential mechanism of the amplification of responses in our coinfection model is IL-1␤-induced upregulation of the receptors responsible for viral infection or detection. Indeed, major-group RVs cause the endogenous release of IL-1␤, which then acts in an autocrine manner to further potentiate inflammatory responses, for example, through upregulation of the RV major group receptor ICAM-1 (18,19,58). However, we found that while IL-1␤ enhanced CXCL8 release from virally infected epithelial cells, it did not augment virally induced ISGs, having no impact on CXCL10 production and in fact modestly reducing CCL5 release, implying that the cooperation of stimuli exerts selective actions on specific pathways.…”
mentioning
confidence: 99%
“…Inhibiting IL-1b or blocking IL-1 receptors prevents virus-induced, toluene diisocyanate-induced, and antigen challenge-induced hyperreactivity in animals (24)(25)(26)(27). In humans with asthma, IL-1b is present in lavage, epithelial cells, and alveolar macrophages (28)(29)(30)(31).…”
mentioning
confidence: 99%